2021
DOI: 10.1021/acs.jafc.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Galloyl Group in B-type Proanthocyanidin Dimers Was Responsible for Its Differential Inhibitory Activity on 3T3-L1 Preadipocytes due to the Strong Lipid Raft-Perturbing Potency

Abstract: The effects of three B-type proanthocyanidin (PA) dimers covering procyanidin B2 (B-0g), procyanidin B2 3′-O-gallate (B-1g), and procyanidin B2 3,3′-di-O-gallate (B-2g) on 3T3-L1 preadipocyte differentiation and the underlying mechanisms were investigated. The results showed that digalloylated B-type PA dimers (B-2g) strongly inhibited 3T3-L1 preadipocyte differentiation through disrupting the integrity of the lipid raft structure and inhibiting the expression of peroxisome proliferator-activated receptor gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…There is increasing evidence which suggests that the structure and function of the lipid rafts play important roles in the cellular biological activities. , For example, changes in the structure of the lipid rafts could affect the differentiation of the 3T3-L1 preadipocytes into mature adipocytes, thereby interfering with the whole-body fuel homeostasis . Furthermore, the results of our earlier studies showed that the effects of polyphenols with different biological activities on the structure of lipid rafts also differed. , Therefore, we inferred that the lipid rafts could fill this gap by linking the properties of chemical substances with their biological activities and offering a better interpretation for the SAR of polyphenols. To test this assumption, we first correlated the interaction between several polyphenols and the lipid rafts with their differentiation-inhibitory effects on 3T3-L1 preadipocytes and found that these interactions and effects were highly positively correlated.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…There is increasing evidence which suggests that the structure and function of the lipid rafts play important roles in the cellular biological activities. , For example, changes in the structure of the lipid rafts could affect the differentiation of the 3T3-L1 preadipocytes into mature adipocytes, thereby interfering with the whole-body fuel homeostasis . Furthermore, the results of our earlier studies showed that the effects of polyphenols with different biological activities on the structure of lipid rafts also differed. , Therefore, we inferred that the lipid rafts could fill this gap by linking the properties of chemical substances with their biological activities and offering a better interpretation for the SAR of polyphenols. To test this assumption, we first correlated the interaction between several polyphenols and the lipid rafts with their differentiation-inhibitory effects on 3T3-L1 preadipocytes and found that these interactions and effects were highly positively correlated.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, the epicatechin-(4β → 8, 2β → O → 7)-epicatechin (A-type EC dimer) displayed a minimal effect on the lipid raft structure of 3T3-L1 preadipocytes and showed a rather low inhibitory effect . Importantly, our previous results showed that polyphenols at physiological concentrations could significantly interfere with the structural integrity of lipid rafts, thereby exerting the ability to inhibit 3T3-L1 preadipocyte differentiation . Therefore, we hypothesized that lipid rafts might be an attractive target for explaining the mechanism underlying the pleiotropic actions of polyphenols as well as for screening bioactive polyphenols.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…As mentioned previously, 22 the mature lipid droplets were marked with Oil Red O (ORO) dye. Differentiation was monitored under a Nikon microscope and quantified at 490 nm by an eluting stain in 100% isopropyl alcohol.…”
Section: Oil Red O Staining and Lipid Quantificationmentioning
confidence: 99%